2013
DOI: 10.1590/s1516-18462013005000029
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da profundidade do palato duro: correlação entre método quantitativo e qualitativo

Abstract: OBJETIVO: verificar correlação entre método quantitativo e qualitativo de avaliação da profundidade do palato duro. MÉTODO: participaram da pesquisa 74 crianças, com dentição mista, submetidas à avaliação fonoaudiológica e odontológica que incluiu moldagem do arco dental maxilar para confecção dos modelos de gesso usados para posterior mensuração. Para análise quantitativa mediu-se largura e profundidade do palato duro ao nível dos primeiros molares, cujos valores foram utilizados para o Índice de Altura Palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
10
0
4
Order By: Relevance
“…The palate is situated in the maxillary region just below the maxillary sinus and the nasal cavity. It is composed of hard and soft palates [ 1 ]. The hard palate is regarded as an important part of the human skull, which contributes to the separation of the oral and nasal cavities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The palate is situated in the maxillary region just below the maxillary sinus and the nasal cavity. It is composed of hard and soft palates [ 1 ]. The hard palate is regarded as an important part of the human skull, which contributes to the separation of the oral and nasal cavities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orofacial myofunctional evaluation includes a visual and subjective inspection of the hard palate through anthroposcopic assessment. Current clinical assessment protocols include evaluation of width and depth of the hard palate (1,2) , because the morphology of the structures of the stomatognathic system are crucial for the correct processing functions of this system (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Current research on orofacial myology is aimed at studying quantitative methods of evaluation that can complement orofacial myofunctional clinical examination. In the literature, there are some resources for quantitative assessment of the hard palate in research whose objective is to compare the dimensions of the hard palate between different clinical groups (4)(5)(6)(7)(8) or compare qualitative and quantitative evaluations of the hard palate (3,9) . However, in order to make the use of such resources feasible in clinical practice, knowledge is required of reference parameters for quantitative analysis of the hard palate according to gender and age.…”
Section: Introductionmentioning
confidence: 99%
“…In another study (14) , the researchers also correlated the quantitative and qualitative methods for the classification of the hard palate of children through measuring and evaluation of three judges. According to the palatal height index, the authors classified the hard palate in high, medium, and low and concluded that, in the qualitative analysis, there was a tendency to consider in some cases the palate as high, differently from what the measurement of depth using the quantitative method indicated.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the cause may have been the high value of standard deviation found in the sample containing 400 skulls, which could have been avoided excluding the skulls that had very deviant values (nonstandard) from the sample. Some studies (12,14,15) carried out quantitative analysis of the depth of the hard palate. It would be interesting to apply a multiple linear regression test in the search for prediction of this variable from other measurements, because it is an important anatomical feature within the speech-language pathology and audiology assessment.…”
Section: Discussionmentioning
confidence: 99%